Answer to ECG Quiz no. 31 - Millar, R. Scott (SA Heart Journal, 2017)
Regular, wide QRS tachycardia is usually VT, even in young people. QRS morphology is the key to differentiating VT from SVT with bundle branch block. P-waves may help to distinguish VT from pre-excited tachycardias. VT from the right ventricle (pseudo LBBB morphology) requires investigation for ARVC.